Lithium adsorbent and preparation method and application thereof
By using block polyether polymers as binders in lithium adsorbents, the hydrophilicity and bonding strength of lithium adsorbents are improved, and the problems of low adsorption efficiency and short service life in the prior art are solved, and the problem of low adsorption efficiency and short service life in the prior art is achieved. More efficient lithium ion extraction and longer service life.
Patent Information
- Application Number
- CN202411325887.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-23
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-09-23
AI Technical Summary
The adsorption efficiency of existing lithium adsorbents is low and the circulation life is not long. It is mainly due to the poor compatibility of polymer binders and precursor powders, which leads to unsolid bonding, the overall adsorbent is not hydrophilic and the infiltration rate is slow. , poor wear resistance.
Block polyether polymers are used as binders, specifically triblock copolymers of polyethylene glycol and polypropylene glycol. Combined with polymer binders, they form amphiphilic materials to improve the hydrophilicity and bonding of adsorbents. Strength, the preparation method includes mixing organic solvents, binders, lithium adsorbent precursors and block polyether polymers, and obtaining lithium adsorbents through granulation and hardening.
It improves the wetting and wear resistance of lithium adsorbents, shortens the mass transfer time of lithium ions, extends the circulation life of adsorbents, and maintains stable performance in salt lake brine.
Smart Images

Figure CN119236890A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium extraction from salt lakes, and specifically relates to a lithium adsorbent and a preparation method and application thereof. Background Art
[0002] The adsorption method of lithium extraction from salt lakes is to use lithium adsorbent to + "The unique adsorption performance, through the continuous "adsorption" and "analysis" process, makes Li + It is concentrated and enriched among many alkali metal ions, and the performance of lithium adsorbent determines the enrichment of Li + key factors.
[0003] At present, the most widely used method for forming and granulating lithium adsorbents is the wet extrusion process, which is to blend and granulate the adsorbent precursor powder, polymer binder and solvent. In order to adapt to this granulation process, the polymer binder is generally a hydrophobic polymer, which makes the overall hydrophilicity of the adsorbent after granulation low, and the infiltration rate of brine is slow, so that the overall adsorption efficiency of the adsorbent is not high. In addition, the polymer binder itself has poor compatibility with the precursor powder, resulting in the binder's weak bonding to the precursor powder during the forming and granulation process, which makes the adsorbent low in strength and poor in wear resistance, and thus leads to a short cycle life. Summary of the invention
[0004] Therefore, the technical problem to be solved by the present invention is to overcome the common shortcomings of low adsorption efficiency and short cycle life of lithium adsorbents in the prior art, thereby providing a lithium adsorbent and a preparation method and application thereof.
[0005] To this end, the present invention provides the following technical solutions.
[0006] In a first aspect, the present invention provides a lithium adsorbent, the raw materials of which include a lithium adsorbent precursor, a binder and a block polyether polymer;
[0007] The block polyether polymer is a triblock copolymer of polyethylene glycol and polypropylene glycol;
[0008] The average molecular weight Mw of the block polyether polymer is 8000-100000; the repeating unit -OCH 2 CH 2 - and -OCH(CH 3 )CH 2 -The molar ratio is 7:3 to 3:7.
[0009] For example, the average molecular weight of the block polyether polymer can be 8400, 10000, 13000, 14600, 15000, 15800, 17000, 19000, 25000, 28700, 32000, 35000, 39500, 42000, 48000, 54000, 55000, 60000, 63700, 68000, 72000, 75000, 79200, 84000, 88000, 91300, 94000, or 98000.
[0010] In a possible implementation, the block polyether polymer is 0.5-5 wt % of the mass of the lithium adsorbent precursor.
[0011] In a possible implementation, the binder is a polymer binder;
[0012] Optionally, the polymer binder has a Mw of 1*10 5 ~15*10 5 ;
[0013] Optionally, the binder includes one or more of polysulfone, polyethersulfone, polyvinylidene fluoride, polyvinyl chloride, chlorinated polyvinyl chloride, cellulose acetate, carboxymethyl cellulose, chitosan, polymethyl methacrylate, polyacrylonitrile, polyurethane, and polystyrene;
[0014] Optionally, the amount of the binder is 10 to 50 wt % of the mass of the lithium adsorbent precursor.
[0015] In one possible implementation, the lithium adsorbent precursor satisfies at least one of the following conditions:
[0016] (1) selected from aluminum-based lithium adsorbent precursors, titanium-based lithium adsorbent precursors, or manganese-based lithium adsorbent precursors;
[0017] Optionally, the aluminum-based lithium adsorbent precursor is xLiCl·2Al(OH) 3 ·nH 2 O, x=0.4~1.0, n=0~10;
[0018] Optionally, the manganese-based lithium adsorbent precursor is Li(H)Mn 2 O 4 、Li(H) 1.6 Mn 1.6 O 4 or Li(H) 1.33 Mn 1.67 O 4 ;
[0019] Optionally, the titanium-based lithium adsorbent precursor is Li(H)2 TiO 3 or Li(H) 4 Ti 5 O 12 ;
[0020] (2) The particle size of the lithium adsorbent precursor is 0.5 to 100 μm, and can be optionally 1 to 10 μm.
[0021] In a second aspect, the present invention provides a method for preparing a lithium adsorbent, comprising:
[0022] An organic solvent, a binder, a lithium adsorbent precursor and a block polyether polymer are mixed and granulated to obtain granules; after the granules are hardened, the organic solvent is removed to obtain the lithium adsorbent.
[0023] In a possible embodiment, the step of mixing the organic solvent, the binder, the lithium adsorbent precursor, and the block polyether polymer further comprises adding an additive;
[0024] Optionally, the additive is used in an amount of 0.1 to 5 wt% of the mass of the lithium adsorbent precursor;
[0025] Optionally, the additive includes one or more of polyvinyl alcohol, PVP K30, PVP K60, PVP K90, PEG-200, PEG-400, PEG-1000, PEG-2000, PEG-6000, sodium bicarbonate, sodium carbonate, potassium bicarbonate, potassium carbonate, Tween 80, Span 40, γ-aminopropyl triethoxysilane, γ-glycidyl ether oxygen propyl trimethoxysilane, vinyl trimethoxysilane, bis-(3-(triethoxysilyl)-propyl)-tetrasulfide. The additive can play a role in pore formation and / or improve surface activity, further improving the adsorption performance of lithium.
[0026] In one possible implementation, an organic solvent, a binder, a lithium adsorbent precursor, and a block polyether polymer are mixed under heating conditions;
[0027] Optionally, the heating temperature is 25°C to 150°C, and optionally 60°C to 100°C.
[0028] In a possible embodiment, the pellets are hardened by immersing the pellets in a coagulation bath. In some embodiments, the coagulation bath is water or an organic solvent in water or ethanol; the organic solvent in the organic solvent in water or ethanol is one or a mixture of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, dimethyl sulfoxide, chloroform, dichloroethane, ethyl acetate; the concentration of the organic solvent in water or ethanol is 0 to 50%, preferably 0 to 20%.
[0029] In a possible embodiment, the organic solvent includes one or more of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, dimethyl sulfoxide, chloroform, dichloroethane, and ethyl acetate;
[0030] Optionally, the amount of the organic solvent is 40 wt% to 100 wt% of the total weight of the binder and the lithium adsorbent precursor.
[0031] In a third aspect, the present invention provides a lithium adsorbent or a lithium adsorbent prepared according to the above method for use in adsorbing and extracting lithium ions in salt lake brine.
[0032] In some embodiments, the mixing device used to mix the organic solvent, the binder, the lithium adsorbent precursor, and the block polyether polymer is selected from a kneader, an internal mixer, and a blender.
[0033] In some embodiments, the extruder used for granulation is selected from any one of a single-screw extruder, a twin-screw extruder and a piston extruder.
[0034] The technical solution of the present invention has the following advantages:
[0035] 1. The raw materials of the lithium adsorbent of the present invention include a lithium adsorbent precursor, a binder and a block polyether polymer; the block polyether polymer is a triblock copolymer of polyethylene glycol and polypropylene glycol; the average molecular weight of the block polyether polymer is 8000 to 100000; the repeating unit -OCH 2 CH 2 - and -OCH(CH 3 )CH 2 -The molar ratio is 7:3 to 3:7.
[0036] The lithium adsorbent of the present invention contains an amphiphilic block polyether polymer, which makes the lithium adsorbent have a certain hydrophilicity, that is, the lithium adsorbent has good wettability, and can make the lithium adsorbent wet a large number of pores in a short time, thereby shortening the mass transfer time of lithium ions and improving the lithium extraction rate; at the same time, because the introduction of the amphiphilic polymer can make the bonding effect of the binder stronger, the lithium adsorbent precursor powder is less likely to fall, and the wear resistance and strength are improved, thereby extending the cycle service life of the adsorbent. In addition, the block polyether polymer defined in the present invention is insoluble in water, which can avoid being dissolved and removed by water during the preparation process of the lithium adsorbent or in the process of extracting lithium from salt lake brine, thereby ensuring the performance of the lithium adsorbent during long-term cyclic use.
[0037] 2. The block polyether polymer is 0.5-5wt% of the mass of the lithium adsorbent precursor. When the amount is limited to this range, the lithium adsorbent can have good hydrophilicity and wear resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0039] Figure 1 This is the relationship between the adsorption amount and the adsorption time. DETAILED DESCRIPTION
[0040] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.
[0041] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.
[0042] Example 1
[0043] This embodiment provides a method for preparing a lithium adsorbent, comprising the following steps:
[0044] (1) Preparation of lithium adsorbent precursor:
[0045] AlCl 3 6H 2 O、LiCl·H 2 O and deionized water were ultrasonically mixed at 75°C for 60 minutes to obtain a mixed solution. The Li / Al molar ratio in the mixed solution was 1.5 / 2, the concentration of lithium ions was 0.075 mol / L, and the concentration of aluminum ions was 0.1 mol / L. The mixed solution and ammonia water (6 mol / L) were simultaneously added dropwise to the reactor. The dropping speed of the mixed solution and ammonia water was 7.5 ml / min, and the stirring speed was 150 rpm. The entire reaction was controlled by a circulating water bath at 90°C. The pH value at the end of the addition was controlled to 7. After the reaction was completed, it was allowed to stand and age for 24 hours at a temperature of 90°C. After filtration, the solid was washed, dried, and crushed to obtain a lithium adsorbent precursor powder LiCl·2Al(OH) with an average particle size of 5 μm. 3 ·H 2 O.
[0046] (2) Weigh 10 kg of the lithium adsorbent precursor powder prepared in (1), 2 kg of polyacrylonitrile (Mw = 500,000, McLean), 9 kg of N,N-dimethylformamide and 0.4 kg of a triblock copolymer of polyethylene glycol and polypropylene glycol (Aladdin Technology Co., Ltd., average molecular weight 15,800, repeating unit -OCH 2 CH 2 - and -OCH(CH 3 )CH 2 - has a molar ratio of 3:7), as well as 0.2kg PVP K90, 0.05kg Tween 80, and 0.1kg γ-glycidyloxypropyltrimethoxysilane, which are mixed at 70°C in an internal mixer until they are uniform, and then extruded and granulated by a piston extruder to obtain a lithium adsorbent semi-finished product, which is hardened by soaking the lithium adsorbent semi-finished product in water, and the solvent contained therein is removed, so as to obtain a granular lithium adsorbent with a particle size of 0.8 to 2.0 mm.
[0047] Example 2
[0048] This embodiment provides a method for preparing a lithium adsorbent, comprising the following steps:
[0049] (1) Preparation of lithium adsorbent precursor:
[0050] AlCl 3 6H 2 O、LiCl·H 2 O and deionized water were ultrasonically mixed at 75°C for 60 minutes to obtain a mixed solution. The Li / Al molar ratio in the mixed solution was 1.5 / 2, the concentration of lithium ions was 0.075 mol / L, and the concentration of aluminum ions was 0.1 mol / L. The mixed solution and ammonia water (6 mol / L) were simultaneously added dropwise to the reactor. The dropping speed of the mixed solution and ammonia water was 7.5 ml / min, and the stirring speed was 150 rpm. The entire reaction was controlled by a circulating water bath at 90°C. The pH value at the end of the addition was controlled to 7. After the reaction was completed, it was allowed to stand and age for 24 hours at a temperature of 90°C. After filtration, the solid was washed, dried, and crushed to obtain a lithium adsorbent precursor powder LiCl·2Al(OH) with an average particle size of 5 μm. 3 ·H 2 O.
[0051] (2) Weigh 10 kg of the lithium adsorbent precursor powder prepared in (1), 2 kg of polyacrylonitrile (Mw = 500,000, MacLean), 9 kg of N-methylpyrrolidone and 0.05 kg of a triblock copolymer of polyethylene glycol and polypropylene glycol (Aladdin Technology Co., Ltd., average molecular weight 39,500, repeating unit -OCH 2 CH 2 - and -OCH(CH 3)CH 2 - has a molar ratio of 7:3), and 0.05kg PEG-6000, are mixed at 70°C with a stirrer until they are uniform, and then extruded and granulated with a piston extruder to obtain a lithium adsorbent semi-finished product, the lithium adsorbent semi-finished product is soaked and hardened in an aqueous solution of 20wt% N-methylpyrrolidone, and then washed with water to remove the solvent contained inside, so as to obtain a granular lithium adsorbent with a particle size of 0.8-2.0mm.
[0052] Example 3
[0053] This embodiment provides a method for preparing a lithium adsorbent, comprising the following steps:
[0054] (1) Preparation of lithium adsorbent precursor:
[0055] AlCl 3 6H 2 O、LiCl·H 2 O and deionized water were ultrasonically mixed at 75°C for 60 minutes to obtain a mixed solution. The Li / Al molar ratio in the mixed solution was 1.5 / 2, the concentration of lithium ions was 0.075 mol / L, and the concentration of aluminum ions was 0.1 mol / L. The mixed solution and ammonia water (6 mol / L) were simultaneously added dropwise to the reactor. The dropping speed of the mixed solution and ammonia water was 7.5 ml / min, and the stirring speed was 150 rpm. The entire reaction was controlled by a circulating water bath at 90°C. The pH value at the end of the addition was controlled to 7. After the reaction was completed, it was allowed to stand and age for 24 hours at a temperature of 90°C. After filtration, the solid was washed, dried, and crushed to obtain a lithium adsorbent precursor powder LiCl·2Al(OH) with an average particle size of 5 μm. 3 ·H 2 O.
[0056] (2) Weigh 10 kg of the lithium adsorbent precursor powder prepared in (1), 1 kg of polymethyl methacrylate (Mw = 350,000, Aladdin Technology Co., Ltd.), 11 kg of N,N-dimethylacetamide and 0.5 kg of a triblock copolymer of polyethylene glycol and polypropylene glycol (Aladdin Technology Co., Ltd., average molecular weight 68,000, repeating unit -OCH 2 CH 2 - and -OCH(CH 3 )CH 2 - has a molar ratio of 3:7) and 0.5kg PVP K60, are mixed at 80°C using a kneader until they are uniform, and then are extruded and granulated using a single-screw extruder to obtain a lithium adsorbent semi-finished product. Finally, the lithium adsorbent semi-finished product is soaked and hardened in an aqueous solution of 5% concentration of N,N-dimethylformamide, and then washed with water to remove the solvent contained inside, so as to obtain a granular lithium adsorbent.
[0057] Example 4
[0058] This embodiment provides a method for preparing a lithium adsorbent, which is basically the same as that of Embodiment 1, except that the amount of the triblock copolymer of polyethylene glycol and polypropylene glycol added is 0.2 kg.
[0059] Example 5
[0060] This embodiment provides a method for preparing a lithium adsorbent, which is basically the same as that of embodiment 1, except that: the repeating unit -OCH 2 CH 2 - and -OCH(CH 3 )CH 2 -The molar ratio is 7:3.
[0061] Comparative Example 1
[0062] This comparative example provides a method for preparing a lithium adsorbent, which is basically the same as Example 1, except that the triblock copolymer of polyethylene glycol and polypropylene glycol is not added.
[0063] Comparative Example 2
[0064] This comparative example provides a method for preparing a lithium adsorbent, which is basically the same as Example 1, except that a triblock copolymer of polyethylene glycol and polypropylene glycol of the same mass (Aladdin Technology Co., Ltd., with an average molecular weight of 1900 and a repeating unit of -OCH 2 CH 2 - and -OCH(CH 3 )CH 2 - with a molar ratio of 9:1) to replace the triblock copolymer of polyethylene glycol and polypropylene glycol in Example 1. The triblock copolymer of polyethylene glycol and polypropylene glycol in this comparative example is used as a porogen in the aqueous phase system. Although the triblock copolymer of polyethylene glycol and polypropylene glycol is added to the raw material, it is removed during the washing process because it is soluble in water.
[0065] Test example
[0066] (1) Adsorption efficiency detection method:
[0067] 500 g (dry weight) of lithium adsorbent particles prepared in the examples and comparative examples were deionized at 50° C. using deionized water until the precursor powder was 0.4 LiCl·2Al(OH) 3 ·H 2O structure (i.e., the lithium adsorbent is activated before adsorption), and then the analyzed lithium adsorbent is placed in a high magnesium-lithium ratio salt lake brine for adsorption, and the adsorption amount of the lithium adsorbent at different times (adsorption 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h, 13h, 14h, 15h, 16h, 17h, 18h, 19h, 20h, 21h, 22h, 23h, 24h) is calculated according to the lithium ion concentration difference in the water sample, and a relationship diagram between the adsorption amount and the adsorption time of each embodiment and the comparative example is drawn. The test results are shown in Figure 1 shown.
[0068] Depend on Figure 1 Comparison of Examples 1 to 5 with Comparative Examples 1 and 2 shows that after adding the block polyether polymer defined in the present invention, the time required for the adsorbent to reach saturated adsorption is shorter and the adsorption efficiency is higher.
[0069] From the comparison between Example 1 and Example 4, it can be seen that the increase in the amount of added block polyether polymer can further shorten the adsorption time required to achieve the same adsorption amount, thereby improving the adsorption efficiency.
[0070] From the comparison between Example 1 and Example 5, it can be seen that the more hydrophilic segments in the block polyether polymer, the shorter the adsorption time required to achieve the same adsorption amount, and the higher the adsorption efficiency. It is proved that the addition of amphiphilic block polyether polymer can improve the overall hydrophilicity of the adsorbent, so that the adsorbent can wet the brine faster, thereby improving the lithium extraction rate and adsorption efficiency.
[0071] (2) Wear rate evaluation method after cyclic use:
[0072] 500 g (dry weight) of lithium adsorbent particles prepared in the embodiment and the comparative example were respectively loaded into the chromatography column, and adsorbed with brine from a salt lake with a high magnesium-lithium ratio for 1 hour, and then analyzed with deionized water at room temperature for 1 hour, and the industrial continuous dynamic operation was simulated for 1000 cycles. The wear rate of the lithium adsorbent after 1000 cycles was calculated based on the mass difference of the adsorbent. The specific test results are shown in Table 1:
[0073] Table 1
[0074]
[0075]
[0076] Wear rate = (mass of lithium adsorbent before operation - mass of lithium adsorbent after 1000 cycles of operation) / mass of lithium adsorbent before operation * 100%
[0077] From the table above, it can be seen that after adding the block polyether polymer, the wear of the lithium adsorbent after cyclic use is reduced, the service life is longer, and the more hydrophilic segments, the lower the wear rate. It is also verified that the addition of the block polyether polymer can make the bonding effect between the lithium adsorbent precursor powder and the binder stronger, and the bonding of the lithium adsorbent precursor powder is more firm.
[0078] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the scope of protection of the invention.
Claims
1. A lithium adsorbent, characterized in that: The raw materials include lithium adsorbent precursor, binder and block polyether polymer; The block polyether polymer is a triblock copolymer of polyethylene glycol and polypropylene glycol; The average molecular weight of the block polyether polymer is 8000-100000; the molar ratio of the repeating units -OCH2CH2- and -OCH(CH3)CH2- in the block polyether polymer is 7:3-3:
7.
2. The lithium adsorbent according to claim 1, characterized in that The block polyether polymer is 0.5-5wt% of the mass of the lithium adsorbent precursor.
3. The lithium adsorbent according to claim 1, characterized in that The binder is a polymer binder; Optionally, the binder includes one or more of polysulfone, polyethersulfone, polyvinylidene fluoride, polyvinyl chloride, chlorinated polyvinyl chloride, cellulose acetate, carboxymethyl cellulose, chitosan, polymethyl methacrylate, polyacrylonitrile, polyurethane, and polystyrene; Optionally, the amount of the binder is 10 to 50 wt % of the mass of the lithium adsorbent precursor.
4. The lithium adsorbent according to claim 1, characterized in that The lithium adsorbent precursor satisfies at least one of the following conditions: (1) selected from aluminum-based lithium adsorbent precursors, titanium-based lithium adsorbent precursors, or manganese-based lithium adsorbent precursors; Optionally, the aluminum-based lithium adsorbent precursor is xLiCl·2Al(OH)3·nH2O, x=0.4-1.0, n=0-10; Optionally, the manganese-based lithium adsorbent precursor is Li(H)Mn2O4, Li(H) 1.6 Mn 1.6 O4 or Li(H) 1.33 Mn 1.67 O4; Optionally, the titanium-based lithium adsorbent precursor is Li(H)2TiO3 or Li(H)4Ti5O 12 ; (2) The particle size of the lithium adsorbent precursor is 0.5 to 100 μm, and can be optionally 1 to 10 μm.
5. A method for preparing the lithium adsorbent according to any one of claims 1 to 4, characterized in that: include: An organic solvent, a binder, a lithium adsorbent precursor, and a block polyether polymer are mixed and granulated to obtain granules; After the pellets are hardened, the organic solvent is removed to obtain the lithium adsorbent.
6. The method for preparing a lithium adsorbent according to claim 5, characterized in that: The step of mixing the organic solvent, the binder, the lithium adsorbent precursor, and the block polyether polymer further includes adding an additive; Optionally, the additive is used in an amount of 0.1 to 5 wt% of the mass of the lithium adsorbent precursor; Optionally, the additive includes one or more of polyvinyl alcohol, PVP K30, PVP K60, PVP K90, PEG-200, PEG-400, PEG-1000, PEG-2000, PEG-6000, sodium bicarbonate, sodium carbonate, potassium bicarbonate, potassium carbonate, Tween 80, Span 40, γ-aminopropyltriethoxysilane, γ-glycidyloxypropyltrimethoxysilane, vinyltrimethoxysilane, and bis-(3-(triethoxysilyl)-propyl)-tetrasulfide.
7. The method for preparing a lithium adsorbent according to claim 5, characterized in that: The organic solvent, the binder, the lithium adsorbent precursor and the block polyether polymer are mixed under heating conditions; Optionally, the heating temperature is 25°C to 150°C, and optionally 60°C to 100°C.
8. The method for preparing a lithium adsorbent according to any one of claims 5 to 7, characterized in that: The pellets are hardened by immersing the pellets in a coagulation bath.
9. The method for preparing a lithium adsorbent according to any one of claims 5 to 7, characterized in that: The organic solvent includes one or more of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, dimethyl sulfoxide, chloroform, dichloroethane, and ethyl acetate; Optionally, the amount of the organic solvent is 40 wt% to 100 wt% of the total weight of the binder and the lithium adsorbent precursor.
10. Use of the lithium adsorbent according to any one of claims 1 to 4 or the lithium adsorbent prepared according to the method according to any one of claims 5 to 9 in adsorbing and extracting lithium ions from salt lake brine.
Citation Information
Patent Citations
Catalyst for reductive amination reaction, and application thereof
CN103920498A
Lithium adsorbent composite granules and preparation method thereof
CN108722372A
Porous composite lithium adsorbent and preparation method thereof
CN113996274A
Catalyst for reductive amination reaction and use thereof
WO2014189222A1
